Análisis de la Importancia del Comercio Justo para la Empresa Exportadora de Rosas Hoja Verde Cía. Ltda. - Castro Jácome, María José (2024)
Fair Trade is a concept developed after the existing exploitation in the productive sectors south of the equatorial line, for the benefit of intermediaries who traded the same products in first world markets. In this study we will review the concept from its beginnings, knowing its historical background. Of course, the underlying concepts and ideas that will allow the structuring of its ideology will be known. Of course, we will also learn about the theory in this respect, as well as the institutions that govern and regulate it. Likewise, the fundamental principles of Fair Trade will be known and will be related to world economic trends, in the public and private areas. Structurally, a summary of these principles will be established and it will be determined that Fair Trade meets the criterion of sustainability in four areas: 1, economic\; 2, labour\; 3, environmental\; and, 4, community. However, in order to meet the objectives of Fairtrade it is necessary for affiliated bodies to make consumers in developed countries aware of the need to consume products made with sustainability criteria. In this way, products under the FairTrade scheme will have added value, quoted in first world markets. Finally, final reflections will be posed in a way that more concretely establishes the objectives sought in this study.